DEVELOPMENT OF INTERACTIVE LEARNING MEDIA BASED ONARTICULATE STORYLINE 3 SOFTWARE ON TEMPERATURE AND HEAT MATERIAL IN SMA NEGERI 14 MEDAN - Khairina, Devi; Rais, Abdul (Journal of Learning and Technology in Physics, 2024)
This study aims to produce interactive learning media based on articulate storyline 3 software to test the feasibility of the developed media, determine the response of students to the developed media and test the effectiveness of Interactive Learning media. This type of research is research and development with a development design model 4D (Define, Design, Development, Disseminate). The subjects of this study were 40 students of Class XI in SMA Negeri 14 Medan. The research instruments used were observation sheet, interview instrument, student response questionnaire and test instrument. Based on the results of the feasibility test by material experts obtained a percentage of 90% with very decent criteria, assessment by media experts is 86% with very decent criteria and assessment by expert users (teachers) is 90% with very decent criteria. The effectiveness of Interactive Learning Media obtained a value calculated with a gain of 0.43. The results were included in the medium category in improving students ' cognitive abilities. Based on these results, it can be concluded that the Interactive Learning media based on articulate storyline 3 software that has been developed is very feasible to be used as a medium in the process of learning physics and can improve students cognitive abilities. Keywords: Interactive Learning Media, 4D Thiagarajan, Articulate Storyline 3